Human dendritic cell line models for DC differentiation and clinical DC vaccination studies - Santegoets, Saskia J. A. M.; Eertwegh, Alfons J. M.; Loosdrecht, Arjan A.; Scheper, Rik J.; Gruijl, Tanja D. (Journal of leukocyte biology, 2008)
Dendritic cells (DC) are increasingly applied in the immunotherapy of cancer. As the development of a standardized DC vaccine product is often hampered by the limited availability of DC precursors and inter‐ and intra‐donor variability, and the preparation of individual vaccines is labor‐intensive, it would be preferable to use DC from a readily available and unlimited source, such as cell lines can provide. It has been described that leukemia‐derived cell lines are able to differentiate into functional DC, creating possibilities for the development of highly reproducible DC vaccines and providing in vitro model systems for in‐depth studies about DC physiology. This review discusses the different human DC cell line differentiation models described so far. Based on the available data, characteristics that determine the ability of leukemia cells to differentiate along the different precursor stages into functional DC will be formulated. In addition, evidence will be provided that the human CD34+ acute myeloid leukemia cell line MUTZ‐3 provides DC that exhibit the functional properties that are crucial for the in vivo generation of CTL‐mediated immunity and thus, currently, represents the most valuable, sustainable model system for myeloid DC differentiation and clinical DC vaccination studies.